The Development of Student Worksheets (LKPD) Approaching Natural Exploration (JAS) Plant Materials Class X SMA - Sari, Yuni Kartika; Abdullah, Muhammad (Journal of Biology Education, 2022)
This study aims to determine the validity and feasibility of the Student Worksheet (LKPD) approach to Exploring the Surrounding Nature (JAS) for Class X High School Plant Materials. This LKPD is a teaching material used for observation activities, contains material, activities and activity guides that are carried out by students independently by utilizing the surrounding environment, and evaluation questions. Research on LKPD development with a JAS approach refers to the development procedure according to Sugiyono (2016) which is adapted to research needs. The procedure for developing LKPD with a JAS approach includes potentials and problems, data collection, product design, design validation, design revisions, product trials, product revisions, and limited production. The results of this study include qualitative data obtained from the validity of the LKPD instrument with the JAS approach and student responses. The results of LKPD validity obtained from media expert validation are 93.73% with very valid criteria, material expert validation is 85.15% with valid criteria, and biology teacher validation is 94.32% with very valid criteria. The level of validity of the JAS components by media expert validators is 95.83% with very valid criteria and by material expert validators 87.50% with valid criteria. Student response data is used to determine student responses to the JAS Approach LKPD and LKPD can be used in online learning. LKPD can be used in online learning with the category of student responses being very positive and the average score of responses reaching 3.31. Thus, the LKPD with the JAS approach is stated to be able to be implemented in learning activities. However, it is still necessary to conduct further trials to determine its effectiveness as an alternative biology teaching material and to determine the ability of LKPD to increase students' motivation to carry out activities during online learning.